Stable photovoltaic output and optically tunable resistive switching in all-inorganic flexible ferroelectric thin film with self-polarization characteristic. (15th September 2021) - Li, Yong; Cui, Xiaxia; Tian, Mengwei; Wang, Guangcheng; Hao, Xihong
Abstract: The immense potential of photo-electrical materials applied in intelligent and wearable electronic devices has motivated many researches on flexible ferroelectric thin film. However, how to enhance stability of output and achieve multifunction is still a challenge. Here, an all-inorganic flexible ferroelectric thin film with Au/Bi2 FeMo0.7 Ni0.3 O6 /LaNiO3 /Nickel foil structure is prepared by sol-gel method. The thin film exhibits excellent photovoltaic stability. The change rates of the short circuit currents and open circuit voltages are less than 5% in different bending states and after bending-releasing cycles, which is attributed to its stable self-polarization characteristic. Furthermore, an optically tunable resistive switching behavior is found in the thin film. The switching voltages and ON/OFF ratio of resistance can be tuned in real time by on-off control of light, demonstrating a correlation between resistive switching and photovoltaic effect. It is proposed that the photovoltaic effect modulates the energy band structure of the thin film, leading to an increased ON/OFF ratio of resistance. This work opens up a promising route to the development of multifunctional flexible photo-electrical materials. Graphical abstract: Image, graphical abstract